Observing incumbent abuses: improving measures of electoral and competitive authoritarianism with new data. Issue 1 (2nd January 2017) - Handlin, Samuel
ABSTRACT: Electoral and competitive authoritarian regimes have become a major focus of comparative research. Yet, finding measures that distinguish these regimes from democracies is challenging, especially for scholars conducting large -N cross-national research, as this conceptual distinction rests on incumbent abuses that are difficult to systematically observe. This article reviews common measures that simply utilize extant regime indicators to draw the line with democracy, demonstrates their poor performance in mirroring a benchmark from case-based measurement, and illustrates the adverse implications for theory building. The article then shows how data on incumbent abuse from the National Elections Across Democracy and Dictatorship (NELDA) and Varieties of Democracy (VDEM) projects can be utilized to construct alternative measures. A NELDA-based measure far outperforms extant alternatives in mirroring the case-based benchmark. The article then discusses why a VDEM-based alternative should be a superior option once data is available and how one might be constructed.